Lower-Limb Sensorimotor Deprivation-Related Brain Activation in Patients With Chronic Complete Spinal Cord Injury - Gao, Feng; Guo, Yun; Chu, Hongyu; Yu, Weiyong; Chen, Zhenbo; Chen, Liang; Li, Jun; Yang, Degang; Yang, Mingliang; Du, Liangjie; Li, Jianjun; Chan, Chetwyn C. H. (Frontiers in Neurology, 2020)
This study aims to investigate functional brain reorganization brought about by the loss of physical movement and sensory feedback in lower limbs in chronic spinal cord injury (SCI). Eleven paraplegia patients with SCI and 13 healthy controls (HCs) were recruited. The experimental task used was a visuomotor imagery task requiring subjects to engage in visualization of repetitive tapping movements of the upper or lower limbs. Blood oxygen level-dependent (BOLD) responses were captured during the experimental task, along with the accuracy rate and the response time. The SCI patients performed worse in the Rey Auditory Verbal Learning Test (RAVLT) and the Trail Making Test. SCI patients had a larger BOLD signal in the left lingual gyrus and right external globus pallidus (GPe) when imagining lower-limb movements. For the upper-limb task, SCI patients showed stronger BOLD responses than the HCs in extensive areas over the brain, including the bilateral precentral gyrus (preCG), bilateral inferior parietal gyrus, right GPe, right thalamus, left postcentral gyrus, and right superior temporal gyrus. In contrast, the HCs displayed stronger BOLD responses in the medial frontal gyrus and anterior cingulate gyrus for both upper- and lower-limb tasks than the SCI patients. In the SCI group, for the upper-limb condition, the amplitudes of BOLD responses in the left preCG were negatively correlated with the time since injury (r = −0.72, p = 0.012). For the lower-limb condition, the amplitudes of BOLD responses in the left lingual gyrus were negatively correlated with the scores on the Short Delay task of the RAVLT (r = −0.73, p = 0.011). Our study provided imaging evidence for abnormal changes in brain function and worsened cognitive test performance in SCI patients. These findings suggested possible compensatory strategies adopted by the SCI patients for the loss of sensorimotor function from the lower limbs when performing a limb imagery task.